SATISFACTION OF NURSING STUDENTS WITH A CLINICAL SIMULATION PRACTICE IN HI-FI SETTINGS - Ruiz Vera, Patricia Irene; Martini, Jussara Gue (My University, 2020)
ABSTRACT Objective: to describe the satisfaction with the practical dimension of the high fidelity clinical simulation settings developed by the nursing students. Method: a quantitative, descriptive and correlational approach. Data collection, questionnaire to assess the nursing students' satisfaction with the simulated clinical experiences in the practice. Scale from 1 to 10, with 10 being the maximum satisfaction value and 1, the minimum satisfaction value. A total of 115 students took part. The ethical requirements were met. Results: satisfaction with the achieved learning: fourth year, mean of 7.08; fifth year, mean of 7.05. Motivation to attend practical classes: fourth year, mean of 7.46; fifth year, mean of 7.16. Dynamism of the practical classes: fourth year, mean of 7.27; fifth year, mean of 6.66. Active participation in the developed settings: fourth year, mean of 7.41; fifth year, mean of 7.30. Interaction with their peers: fourth year, mean satisfaction greater than 8.14; fifth year, mean of 7.45. Interaction with the teachers: both classes showed a mean of 7.73. Satisfaction with the degree of difficulty of the settings: fourth year, mean of 7.25; fifth year, mean of 7.32. Productivity during the practical classes: fourth year, mean of 7.12; fifth year, mean of 6.95. Conclusion: fourth year showed greater satisfaction with the practice, over 70%; and fifth year, a satisfaction level of approximately 60% of the options.
Keywords: nursing students; clinical competence; simulation; personal satisfaction teaching; learning